Structure of an RNA aptamer in complex with the fluorophore tetramethylrhodamine. Issue 2 (22nd November 2019) - Duchardt-Ferner, Elke; Juen, Michael; Bourgeois, Benjamin; Madl, Tobias; Kreutz, Christoph; Ohlenschläger, Oliver; Wöhnert, Jens
Abstract: RNA aptamers—artificially created RNAs with high affinity and selectivity for their target ligand generated from random sequence pools—are versatile tools in the fields of biotechnology and medicine. On a more fundamental level, they also further our general understanding of RNA-ligand interactions e. g. in regard to the relationship between structural complexity and ligand affinity and specificity, RNA structure and RNA folding. Detailed structural knowledge on a wide range of aptamer–ligand complexes is required to further our understanding of RNA–ligand interactions. Here, we present the atomic resolution structure of an RNA–aptamer binding to the fluorescent xanthene dye tetramethylrhodamine. The high resolution structure, solved by NMR-spectroscopy in solution, reveals binding features both common and different from the binding mode of other aptamers with affinity for ligands carrying planar aromatic ring systems such as the malachite green aptamer which binds to the tetramethylrhodamine related dye malachite green or the flavin mononucleotide aptamer.